The Quality of Seniors’ Life in Their Natural Environment - Lachytová, Lenka; Kalanin, Peter (Journal of Vasyl Stefanyk Precarpathian National University, 2016)
The aim of the research study is to investigate the quality of life of seniors at home and their satisfaction in the domains of physical health, survival, social relations and the environment itself. Design studio. We conducted the study on a sample of 80 respondents / seniors living at home in Vranov nad Topľou. For processing the obtained data, we used the following statistical methods - the Fisher's F-test and Student's t-test. For detecting the data from respondents we chose an anonymous standardized questionnaire WHOQOL-BREF (World Health Organization Quality of Life - BREF), which is a shortened version of the WHOQOL-100. As completion of this study is the implementation of mechanisms supporting the quality of life of seniors in a natural environment with an emphasis on preventive measures of social policy to maintain a reasonable quality of life